A correlation of lactate dehydrogenase enzyme levels in pregnancy induced hypertensive disorders with severity of disease, maternal and perinatal outcome - Bhave, Neha V.; Shah, Parmanand K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A spectrum of hypertensive disorders in pregnancy contribute to maternal and perinatal morbidity and mortality. For prediction and early diagnosis of preeclampsia various biochemical markers, vascular function test and renal markers have been developed. The objective of the study is to measure the lactate dehydrogenase enzyme (LDH) levels in pregnant women with pregnancy induced hypertensive disorders and correlate the levels with the severity of condition, maternal and the perinatal outcome. Methods: In this prospective observational study, a total of 150 pregnant women were studied. Out of these 150 women, 30 women had normal blood pressure, 30 women had gestational hypertension, 30 women had mild preeclampsia, 30 women had severe preeclampsia and 30 women had eclampsia. The serum LDH levels were measured in third trimester and patients followed up until early postpartum period and babies were followed up till early neonatal period to assess the maternal and neonatal outcomes. Results: Higher lactate dehydrogenase enzyme (LDH) levels were observed in pregnant women with severe form of hypertensive disorder and those who had a poor maternal and perinatal outcome. This is statistically significant (p<0.001). Conclusions: Lactate dehydrogenase enzyme (LDH) level is a useful biochemical marker to assess and predict the severity of disease, maternal and perinatal outcome as higher levels of the enzyme are associated with worsening severity of disease, a poor maternal and perinatal outcome.